The videoconference. A new approach to the principle of procedural immediation - Tayro Tayro, Erwin Arthur (2016)
The information and communication technologies are a set of techniques used for handling all kinds of information, which have been adopted by the administration of justice systems, including Peru. One of the components of these technologies is videoconferencing, which is a communication system that transmits and receives audio, image and data signals between two or more remotely located sites, in real time; creating a virtual reality. For the traditional doctrine, the principle of immediacy manifests, provided there is actual physical presence of the judge, procedural test subjects and bodies, not support means or intermediaries; but for the new concept, the principle of immediacy relationship further comprises the generated virtual computing environments, between the judicial and procedural subjects, test bodies and between them and those who are in geographically distant locations. Currently in Peru, there is a legal framework that validates this technological means, as a procedural tool to verify hearings and proceedings in criminal procedure.